Comparative analysis of β-glucan content in wild and cultivated barley (Hordeum vulgare) - DON, MUTHANTHIRIGE; NISHANTHA, LALITH CHANDARA; ZHAO, XIAN; JEEWANI, DIDDUGODAGE CHAMILA; XING, GUANGWEI; BIAN, JIANXIN; NIE, XIAOJUN; SONG, WEINING (The Indian Journal of Agricultural Sciences, 2018)
β-glucan is an important element found in cereal cell walls, which is tremendously beneficial to human health and significant in industrial produce. Although some studies have been performed to investigate the β-glucan content in cultivated barley (Hordeum vulgare L.), little is known about it in wild barley, particularly the difference of β-glucan content between wild and cultivated varieties. In this study, β-glucan contents in wild barley from Fertile Crescent, Central Asia, Tibet, and cultivated varieties from the representative regions worldwide were systematically investigated and compared using the mixed-linkage β-glucan assay. Results showed that the mean β-glucan content of wild accessions and cultivated varieties were 5.17 % and 3.81 %, and the Coefficient of Variation (CV %) is 24.18 % and 18.11 % respectively. When statistically analysed, there was a significant variation (p≤ 0.001) of β-glucan content in wild and cultivated barely samples and, wild barley showed higher β-glucan content and higher genetic variation. This study provides the elite germplasm for barley β-glucan genetic improvement programs, and also shed light to trace barley domestication in relation to grain metabolite view.